1993
DOI: 10.1897/1552-8618(1993)12[1813:bafosi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and Fate of Surfactants in Soil

Abstract: Although a growing number of investigations have dealt with selected aspects of the behavior of surfactants in soil and their effects on various soil properties, systematic approaches like those applied to pesticides or heavy metals are still rare. Considering that soil is exposed to a considerable quantity of surfactants, it would appear necessary to do more intensified research in this field. Based on a comprehensive review of the literature, the author briefly outlines the behavior and fate of surfactants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
(4 reference statements)
0
9
0
Order By: Relevance
“…After irrigation with graywater, surfactants may accumulate in soil. Whereas some studies have shown potential negative effects as a result of surfactants accumulation in soil, there is still little data available on the effects of surfactants on soil physical and chemical quality (Abu-Zreig, 2003;Kuhnt, 1993;Wiel-Shafran et al, 2006). Some recent studies on graywater reuse for irrigation have shown accumulation of surfactants ranging from 0.02 to 0.7 mg/kg (Negahban-Azar et al, 2012, Travis et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…After irrigation with graywater, surfactants may accumulate in soil. Whereas some studies have shown potential negative effects as a result of surfactants accumulation in soil, there is still little data available on the effects of surfactants on soil physical and chemical quality (Abu-Zreig, 2003;Kuhnt, 1993;Wiel-Shafran et al, 2006). Some recent studies on graywater reuse for irrigation have shown accumulation of surfactants ranging from 0.02 to 0.7 mg/kg (Negahban-Azar et al, 2012, Travis et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies on graywater reuse for irrigation have shown accumulation of surfactants ranging from 0.02 to 0.7 mg/kg (Negahban-Azar et al, 2012, Travis et al, 2010. The effect of surfactants on soil-water conditions is highly dependent on soil composition and surfactants characteristics (Kuhnt, 1993). It has been reported that percolation and infiltration rate of the soil may be altered in the presence of surfactants (Kuhnt, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reader is directed to a number of other tant and the retention behavior of pure water in the same porous medium. An approach that is commonly papers that provide general information about surfactants and surfactant use in subsurface remediation (e.g., used to describe the effect of a surfactant on therelationship in air-water systems is based on scaling the West and Harwell, 1992;Kuhnt, 1993;Edwards et al, 1994;Sabatini et al, 1996Sabatini et al, ,1998Mulligan et al, 2001).…”
mentioning
confidence: 99%